The Effect of Computer Network Learning Using Cisco Packet Tracer on Student Learning Outcomes a SMK Negri 2 Doloksanggul - Ayuna Sianturi; Albiner Siagian; Justice Z. Panggabean (Outline Journal of Education, 2025)
This study aims to analyze the effect of computer network learning using Cisco Packet Tracer on student learning outcomes at SMK Negeri 2 Doloksanggul. The research employed a quantitative method with a pre-test and post-test Non-Equivalent Control-Group Design. The population consisted of 30 students in the experimental class (using Cisco Packet Tracer) and 30 students in the manual class (without Cisco Packet Tracer). Before hypothesis testing, classical assumption tests, including normality, homogeneity, and initial ability difference tests, were conducted. The results showed that the data was not normally distributed and not homogeneous, so non-parametric statistical analysis (Mann Whitney and Wilcoxon tests) was used. The initial ability difference test showed no significant difference between the two classes, allowing hypothesis testing to be performed on the post-test data. Descriptive analysis indicated a significant increase in learning outcomes in the experimental class, where students transitioned from moderate or bad to good after using Cisco Packet Tracer. Mann Whitney test results showed a higher mean rank in the experimental class, while Wilcoxon test results (p = 0.00) indicated a significant positive effect. In conclusion, Cisco Packet Tracer significantly improved student learning outcomes in Network Infrastructure Administration at SMK Negeri 2 Doloksanggul.